Characterization of Gαo role on neuritogenesis: a focus on the Gαo-Amyloid precursor protein complex - Dias, Roberto Alexandre dos Santos (2017)
Gαo is the most abundant Gα subunit present in the brain, however, its specific functions are still far from clear. Studies of the signaling pathways modulated by Gαo have uncovered potential roles for Gαo in the development of the nervous system, especially in neuritogenesis. The characterization of Gαo interactome has also been crucial for the better understanding of this protein’s functions. One of the Gαo interacting proteins is the amyloid precursor protein (APP), a protein that is involved in several physiological functions, such as cell survival, neuronal migration, and neuronal differentiation. APP is also best known for its involvement in Alzheimer’s Disease (AD). APP binds and activates Gαo, an interplay that was associated with neuronal migration and AD. However, so far, no published study has investigated the effects of the APP-Gαo interaction on neuritogenesis. The main goal of this work was thus to characterize Gαo role on neuritogenesis by focusing the research on the neuritogenic effects of the Gαo-APP complex. First, by using SH-SY5Y neuroblastoma cells, we studied the impact of APP serine 655 (S655) phosphorylation on the APP-Gαo interaction. Through the use of two APP mutants mimicking the phosphorylated and dephosphorylated state of S655, SE and SA APP respectively, we have demonstrated that S655 phosphorylation increases APP efficiency to bind and activate Gαo. Moreover, we present evidence that APP modulates Gαo neuritogenic effects in a phosphodependent mechanism. STAT3 and ERK1/2 signaling displayed a sequential activation on this neuritogenic mechanism, with STAT3 being mainly involved in the formation of new processes, while ERK1/2 was more involved in neuritic elongation. We also present data supporting a role for the APP-Gαo complex on dendritogenesis in rat primary neuronal cultures. The second part of this work focused on unraveling the mechanisms involved in the control of APP and Gαo cellular protein levels. We identified the lysosome as a new pathway by which Gαo is degraded, as an effect of SA APP overexpression. We also provide evidence that this degradation mechanism might be part of chaperone-mediated autophagy, through which APP-Gαo signaling might be regulated. Finally, due to our interest in studying neuronal differentiation and a lack of reliable tools to analyze phase contrast images, we developed NeuronRead, an ImageJ macro capable of semi-automated analysis of both phase contrast and fluorescence neuronal images. NeuronRead was extensively validated and used to monitor SH-SY5Y differentiation upon modulation of Gαo activity. With this work, we delivered new data that advances knowledge on the function and regulation of the Gαo-APP complex in a neuronal context, and provided the scientific community with a new tool for the study of neuronal differentiation.